PERAN KEPEMIMPINAN KETUA YAYASAN DALAM MENINGKATKAN KECERDASAN EMOSIONAL (EQ) DILEMBAGA PENDIDIKAN MTs GUPPI TRIRAHAYU KEC. NEGERI KATON KAB. PESAWARAN TAHUN PELAJARAN 2023/2024 - Haris Fahrudin (UNISAN JURNAL, 2024)
Leadership Role of Ketua Yayasan have connection integration with Intelligence Emotional at the Institute Education Whereas study this aim for knowing and reveal Leadership Role of Ketua Yayasan In Improving Intelligence Emotional ( Eq ) In Institutions Education MTs Guppi Trirahayu East Year Lesson 2023/2024. This research is descriptive qualitative research focused on field research, while the object of this research is the Leadership Role of the Chair of the Foundation in Improving Emotional Intelligence ( Eq ) in Educational Institutions MTs Guppi Trirahayu District. Katon District Pesawaran Academic Year 2023/2024. Data collected through documentation , interviews , and observation , then the data were analyzed with use various stages analysis like data reduction , data presentation , withdrawal conclusion and data verification .The results of the study show that the Leadership of the Chairperson of the Foundation Based on Emotional Intelligence ( Eq ) in the MTs Guppi Trirahayu District. Katon District Pesawaran Educational Institution is : 1. ) Chairperson of the Educational Institution Foundation MTs Guppi Trirahayu District. Katon District Pesawaran has a high commitment to self-vision in the future. 2.) The head of the foundation takes an emotional approach to all residents within the educational institution. 3.) Anatomy-neurology of leadership Head of the foundation, When in a problem, it doesn’t drag on to the problem they are facing, they will view the problem from a positive side so they can make the best decision. own strengths and limitations, able to control emotions and demonstrate honesty and integrity, trustworthiness.